2015
DOI: 10.1002/aic.14935
|View full text |Cite
|
Sign up to set email alerts
|

Ni‐Al2O3/Ni‐foam catalyst with enhanced heat transfer for hydrogenation of CO2 to methane

Abstract: Monolithic Ni‐Al2O3/Ni‐foam catalyst is developed by modified wet chemical etching of Ni‐foam, being highly active/selective and stable in strongly exothermic CO2 methanation process. The as‐prepared catalysts are characterized by x‐ray diffraction scanning electron microscopy, inductively coupled plasma atomic emission spectrometry, and H2‐temperature programmed reduction‐mass spectrometry. The results indicate that modified wet chemical etching method is working efficiently for one‐step creating and firmly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 56 publications
4
62
0
Order By: Relevance
“…The steady‐state rate has the highest value for a stoichiometric mixture with 38.42 µmol g −1 s −1 . The TOF for the temperature of 300 °C and the pressure of 2 bar has a value of 0.143 s −1 , which is in good agreement with the value reported by Li et al with 0.1 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The steady‐state rate has the highest value for a stoichiometric mixture with 38.42 µmol g −1 s −1 . The TOF for the temperature of 300 °C and the pressure of 2 bar has a value of 0.143 s −1 , which is in good agreement with the value reported by Li et al with 0.1 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The turnover frequency (TOF) at 250 °C was calculated as 0.02 s -1 or as 0.08 s −1 at 300 °C. The TOFs for Ni/Al2O3 methanation catalysts reported in the literature cover a broad range between 0.69 s −1 [11], 0.10 s -1 [18], 0.041-0.097 s −1 [12] and 0.5 × 10 −3 -2.4 × 10 −3 s −1 [17]. The achieved TOFs correspond to typical dimensions; however, it is difficult to compare the results due to the diverse reaction conditions applied in these studies.…”
Section: Operando Qexafs Studies Under Transient Reaction Conditionsmentioning
confidence: 99%
“…Ni-based catalysts generally achieve good activity. In addition, due to the low cost and high activity, Ni catalysts have emerged as the most commonly-used methanation catalysts [11][12][13][14][15][16][17][18], since more active Ru catalysts [19,20] suffer from the high price of the noble metal. The most relevant catalyst support material in industrial methanation reactions is reported to be γ-Al 2 O 3 with a high surface area [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The three strong peaks at 2 θ =44.5, 51.8, and 76.3° were assigned to the Ni (1 1 1), (2 0 0), and (2 2 0) planes of the Ni‐foam (JCPDS No. 04‐0850) only in the MoS 2 ‐Al 2 O 3 /Ni‐foam catalyst. In addition, peaks for the Ni 3 S 2 phase observed in the MoS 2 ‐Al 2 O 3 /Ni‐foam catalyst at 2 θ =31.1, 37.9, 49.7, 50.1, and 55.2° correspond to Ni 3 S 2 (1 1 0), (0 0 3), (1 1 3), (2 1 1), and (1 2 2) (JCPDS No.…”
Section: Figurementioning
confidence: 97%